2018
DOI: 10.3892/etm.2018.6403
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the effect of brazilin on biofilms of Staphylococcus aureus

Abstract: Biofilms significantly enhance antibiotic resistance by inhibiting penetration of antibiotics and are shielded from the immune system via the formation of an extracellular polymeric matrix. Innovative and novel approaches are required for the inhibition of biofilm formation and treatment of biofilm-associated infectious diseases. In the current study, a biofilm model of Staphylococcus aureus was established in vitro to explore inhibitory effects of brazilin (BN) on biofilm formation and to evaluate damaging ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Brazilin, isolated from Caesalpinia sappan L, suppresses the biofilm formation and destroys biofilm of S. aureus possibly by inhibiting extracellular polysaccharide secretion via modulation of icaA and icaR . Moreover, extracts of wheat bran and Brazilian peppertree also exhibit an inhibitory effect on biofilm formation by S.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Brazilin, isolated from Caesalpinia sappan L, suppresses the biofilm formation and destroys biofilm of S. aureus possibly by inhibiting extracellular polysaccharide secretion via modulation of icaA and icaR . Moreover, extracts of wheat bran and Brazilian peppertree also exhibit an inhibitory effect on biofilm formation by S.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Several other plant-derived phenolic compounds have already been discussed in the work by Wu et al, including chalcone [106], resveratrol ( [107], phloretin [104], alfa-cyperone [87], curcumin [108], osthole [105], and brazilin [109]. Among these, resveratrol (Table 11) was active against α-hemolysin [107] and, used in combination with vancomycin, inhibited biofilm formation.…”
Section: Other Phenolic Compoundsmentioning
confidence: 99%
“…Different studies demonstrated its multiple biological properties, including immune system modulatory, antioxidant, anti-inflammatory, antiplatelet, antihepatotoxicity, and antitumor activities [62], as well as its antimicrobial activity [63]. In 2018, Peng and collaborators used a biofilm model of S. aureus to establish in vitro inhibitory effects of brazilin on biofilm formation [19]. Indeed, this molecule was able to inhibit and destroy S. aureus biofilm, to reduce the production of the extracellular polymeric matrix and to inhibit the QS system, thus supporting its use as a novel drug and treatment strategy for S. aureus biofilm-associated infections [19].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…In 2018, Peng and collaborators used a biofilm model of S. aureus to establish in vitro inhibitory effects of brazilin on biofilm formation [19]. Indeed, this molecule was able to inhibit and destroy S. aureus biofilm, to reduce the production of the extracellular polymeric matrix and to inhibit the QS system, thus supporting its use as a novel drug and treatment strategy for S. aureus biofilm-associated infections [19].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation